Urban expansion of boa vista (rr) and the reflections on socioespacial inequality - Oliveira, Janaine Voltolini de; Costa, Maria Clélia Lustosa (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
The article discusses the urban expansion of Boa Vista and its reflections on social and spatial inequality. The only Brazilian capital above the equator, in the northernmost state of the country, Boa Vista has more than quadrupled its population in the last decades, especially since the recognition of Roraima as a state by the Federal Constitution of 1988 and today it concentrates more than 63% of all the population of this unit of the federation. With a mixed approach, a descriptive nature and a bibliographical and documentary research, the study reveals that the rapid urban expansion of Boa Vista significantly altered, besides the city's spatial model, the environment and the social relations established in it, although the municipality has shown improvements in social vulnerability indexes, socio-spatial inequality deepen.
Keywords: Boa Vista; Espaço urbano; Expansão urbana; Desigualdade socioespacial.